Endogenous development, pathogenicity and host specificity of Eimeria cahirinensis Couch, Blaustein, Duszynski, Shenbrot and Nevo, 1997 (Apicomplexa: Eimeriidae) from Acomys dimidiatus (Cretzschmar 1826) (Rodentia: Muridae) from the Near East - Kvicerová, Jana; Ptácková, Pavla; Modrý, David (Parasitology research, 2007)
Eimeria cahirinensis Couch et al. 1997 was found in faecal samples of Acomys dimidiatus from three different localities in the Near East. Twenty-two of 104 (21%) A. dimidiatus trapped on both the south- and north-facing slopes of "Evolution Canyon", Lower Nahal Oren, Mt. Carmel, Israel in August 2001 and 2002 were infected with E. cahirinensis. Oocysts were also obtained from a single individual of A. dimidiatus trapped in Wadi Ramm, Jordan in the summer of 1999. Laboratory-reared spiny mice (Acomys spp.) were inoculated to determine the prepatent and patent period, sporulation time, site of infection, immunogenicity, pathogenicity, pathology and morphology of endogenous stages of E. cahirinensis. Both asexual and sexual stages were localised in the apical part of duodenal and jejunal villi. An experimental inoculation of representatives of several rodent genera revealed the host range of E. cahirinensis to be limited to the genus Acomys.
Keywords: Oocysts; Eimeria; Feces; Female; oocysty; Host-Parasite Interactions; Animals; feces; ženské pohlaví; Murinae; mužské pohlaví; Male; interakce hostitele a parazita; zvířata